De novo shoot regeneration from root cultures of garcinia indica choiss - Deodhar, Swapna R.; Thengane, R. J.; Thengane, Shubhada Ratnakar (Indian Journal of Experimental Biology, 2008)
Roots of plantlets of Garcinia indica when cultured for long time on half strength MS medium supplemented with BAP (0.44-2.22 mu M) showed production of de novo shoots. Roots attached to mother plant showed more number of shoots, while excised root segments produced lesser shoots. Shoots (0.5-0.8 cm) were transferred to elongation medium consisting of Woody Plant Medium (WPM) supplemented with BAP (4.44-22.69 mu M), IAA (5.71 mu M and kinetin (4.65 mu M). It was observed that shoot length increased to 1-2 cm. WPM medium supplemented with NAA (2.69-10.74 mu M) and IBA (4.90 mu M) induced rooting within 20-25 days. Using the present protocol, 20-25 plantlets could be regenerated from single root explant within 3 to 4 months. The protocol has potential for large scale production of elite plants.
Keywords: Garcinia indica; guttifereae; organogenesis; roots; shoots